Genetic mannose binding lectin deficiency is associated with airway microbiota diversity and reduced exacerbation frequency in COPD. Issue 6 (3rd November 2017) - Dicker, Alison J; Crichton, Megan L; Cassidy, Andrew J; Brady, Gill; Hapca, Adrian; Tavendale, Roger; Einarsson, Gisli G; Furrie, Elizabeth; Elborn, J Stuart; Schembri, Stuart; Marshall, Sara E; Palmer, Colin N A; et al.
Abstract : Background: In cystic fibrosis and bronchiectasis, genetic mannose binding lectin (MBL) deficiency is associated with increased exacerbations and earlier mortality; associations in COPD are less clear. Preclinical data suggest MBL interferes with phagocytosis of Haemophilus influenzae, a key COPD pathogen. We investigated whether MBL deficiency impacted on clinical outcomes or microbiota composition in COPD. Methods: Patients with COPD (n=1796) underwent MBL genotyping; linkage to health records identified exacerbations, lung function decline and mortality. A nested subcohort of 141 patients, followed for up to 6 months, was studied to test if MBL deficiency was associated with altered sputum microbiota, through 16S rRNA PCR and sequencing, or airway inflammation during stable and exacerbated COPD. Findings: Patients with MBL deficiency with COPD were significantly less likely to have severe exacerbations (incidence rate ratio (IRR) 0.66, 95% CI 0.48 to 0.90, p=0.009), or to have moderate or severe exacerbations (IRR 0.77, 95% CI 0.60 to 0.99, p=0.047). MBL deficiency did not affect rate of FEV1 decline or mortality. In the subcohort, patients with MBL deficiency had a more diverse lung microbiota (p=0.008), and were less likely to be colonised with Haemophilus spp. There were lower levels of airway inflammation in patients with MBL deficiency. Interpretation: Patients with MBL deficient genotype with COPD have a lower risk of exacerbations and a more diverse lung microbiota. This is the first study to identify a genetic association with the lung microbiota in COPD.